Penyelenggaraan Pelayanan Publik Selama Pandemi Covid-19 di Kota Batam - Abue Abue; Winsherly Tan (Wajah Hukum, 2022)
The implementation of public services during the Covid-19 pandemic in Batam City must continue to be carried out in accordance with applicable minimum service standards for the realization of community legal protection and certainty. The purpose of this study is to find out and examine how the implementation of public services in Batam City during the Covid-19 pandemic. The research method in this writing is empirical juridical with primary data types through observations, distributing questionnaires to 130 people and interviews with 3 (three) recipients of public services in Batam City and secondary data consisting of primary legal materials and secondary legal materials the results of the research show that the implementation of public services during the Covid-19 pandemic in Batam City is still not running effectively and efficiently, even though the government has tried to optimize online services to reduce the crowd, in the end, service recipients or the public still have to provide face-to-face services.